Flight, fragility and furthering stability in Yemen - Mooney, E (Refugee Studies Centre, University of Oxford, 2013)
The existence of a large number of refugees or internally displaced persons in a country is considered a primary indicator of instability.1 By this measure, and all others, Yemen is one of the world’s most fragile states. Less well understood is how this context affects the vulnerability of refugees, IDPs and migrants themselves and what can be done to strengthen protection for them.